2005
DOI: 10.1111/j.1365-2753.2005.00581.x
|View full text |Cite
|
Sign up to set email alerts
|

A signal detection approach to patient–doctor communication and doctor‐shopping behaviour among Japanese patients

Abstract: These results imply the following: (1) a patient's inability to understand a doctor's explanation about treatment, which results from a large gap between the perceptions of the patient and those of the doctor, is the most significant predictor of doctor-shopping behaviour, and (2) in the context of favourable patient-doctor interactions, when doctors feel their explanations are insufficient, they may be able to prevent doctor-shopping behaviour by providing relatively thorough explanations about treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 19 publications
1
31
0
Order By: Relevance
“…Patient expectations and attitudes play important roles in their evaluation of a service; therefore we believe that real satisfaction occurs when it matches knowledge. It has been shown that communication with the pharmacist at community pharmacies or communication with the physician during the examination is strongly related to patient satisfaction [9,18].…”
Section: ،٤ ‫ﺍﻟﻌﺪﺩ‬ ‫ﻋﴩ،‬ ‫ﺍﳋﺎﻣﺲ‬ ‫ﺍﳌﺠﻠﺪ‬ ‫ﺍﻟﻌﺎﳌﻴﺔ،‬ ‫ﺍﻟﺼﺤﺔ‬ ‫ﻣﻨmentioning
confidence: 99%
“…Patient expectations and attitudes play important roles in their evaluation of a service; therefore we believe that real satisfaction occurs when it matches knowledge. It has been shown that communication with the pharmacist at community pharmacies or communication with the physician during the examination is strongly related to patient satisfaction [9,18].…”
Section: ،٤ ‫ﺍﻟﻌﺪﺩ‬ ‫ﻋﴩ،‬ ‫ﺍﳋﺎﻣﺲ‬ ‫ﺍﳌﺠﻠﺪ‬ ‫ﺍﻟﻌﺎﳌﻴﺔ،‬ ‫ﺍﻟﺼﺤﺔ‬ ‫ﻣﻨmentioning
confidence: 99%
“…Due to the limitations of database, the only two demographic variables that were analyzed were age and gender, which were reported factors related to doctor shopping [5,[14][15][16]. Because a patient's healthcare seeking behavior might be affected by social factors such as education, age was stratified into the following groups: 0-5, 6-11, 12-17, 18-24, 25-34, 35-44, 45-54, 55-64, and 65+ years of age for analysis.…”
Section: Demographic Variablesmentioning
confidence: 99%
“…While usage varies within previous literature, in general, the term can refer to the following: (a) changing doctors without professional advice or referral during a single illness episode [1]; (b) consulting two or more doctors for a single disease [2,3]; (c) visiting a clinic with multiple doctors for the same disease [4]; and (d) using several doctors simultaneously [5]. No matter which definition, doctor shopping can result in the wastage and depletion of health resources [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Miscommunication [22,23] and misunderstandings [24] between patients and treatment providers are common, and patients are often dissatisfied with the care they receive [23]. These factors are shown to greatly influence patients’ doctor shopping behavior [2]. …”
Section: Introductionmentioning
confidence: 99%